Transcriptional analysis of nitrogen fixation in Paenibacillus durus during growth in nitrogen-enriched medium - Mardani Abdul Halim; Choo, Quok-Cheong; Ghazali Hamzah Amir; Mustafa Wajidi; Nazalan Najimudin (Wiley-Blackwell Publishing, 2021)
Paenibacillus durus strain ATCC 35681T is a Gram-positive diazotroph that displayed capability of fixing nitrogen even in the presence of nitrate or ammonium. However, the nitrogen fixation activity was detected only at day 1 of growth when cultured in liquid nitrogen-enriched medium. The transcripts of all the nifH homologues were present throughout the 9-day study. When grown in nitrogen-depleted medium, nitrogenase activities occurred from day 1 until day 6 and the nifH transcripts were also present during the course of the study albeit at different levels. In both studies, the absence of nitrogen fixation activity regardless of the presence of the nifH transcripts raised the possibility of a post-transcriptional or post-translational regulation of the system. A putative SigA box sequence was found upstream of the transcription start site of nifB1, the first gene in the major nitrogen fixation cluster. The upstream region of nifB2 showed a promoter recognizable by SigE, a sigma factor normally involved in sporulation.